Peradaban Islam Era Nabi Muhammad S.A.W. - I Wayan Nain Febri; Muhammad Muttaqien (Mahesa Research Center, 2023)
This article seeks to discuss Islamic ideas and civilisation during the time of the Prophet Muhammad S.A.W., as well as the function and strategic importance of the Mosque, Baitul Mal, and Fathul Makkah. The problem focuses on the development of Islamic thinking and civilisation during the time of the Prophet Muhammad SAW, as well as the role and strategic position of the Mosque, Baitul Mal, and Fathul Makkah. In order to approach this problem, theoretical references from a variety of subject-relevant specialists located in books and journals are used. Literature is used to collect and interpret qualitative data. This study indicates that Islamic thinking and civilization in the classical period attempted to spread Islamic treatises as a new way of life over the Arabian Peninsula by describing the dynamics of Muslim society. In the Pre-Islamic Arab culture, also known as the Jahiliyah Era (ignorance), there was a lack of religious, social, and political understanding, as well as awareness of Allah SWT. As for the growth of Islamic civilisation in the time of the Prophet Muhammad, such as through mosques, Baitul mal, and at the time of the fathu Makkah event, examples include mosques, Baitul mal, and the fathu Makkah event. In its early days, this mosque served as an Islamic educational institution, therefore it arranged studies in the form of talks, lectures, and learning models, each of which had its own form or format according to the level of Muslim community development at the time. Prophet Muhammad SAW also initiated the construction of Baitul Mal, which served as a muassasah (institution), managed governmental expenditures and income, and served as a repository for Muslim assets. As for the Fathu Makkah incident serves as a reminder to Muslims and everyone else that human values must always take precedence, regardless of the circumstances.